The Oxytocin-Oxytocin Receptor System and Its Antagonists as Tocolytic Agents - Nikolaos Vrachnis; Fotodotis M. Malamas; Stavros Sifakis; Efthymios Deligeoroglou; Zoe Iliodromiti (International Journal of Endocrinology)
Oxytocin, a hormone involved in numerous physiologic processes, plays a central role in the mechanisms of parturition and lactation. It acts through its receptor, which belongs to the G-protein-coupled receptor superfamily, while Gq/phospholipase C (PLC)/inositol 1,4,5-triphosphate (InsP3) is the main pathway via which it exerts its action in the myometrium. Changes in receptor levels, receptor desensitization, and locally produced oxytocin are factors that influence the effect of oxytocin on uterine contractility in labor. Activation of oxytocin receptor causes myometrial contractions by increasing intracellular Ca+2 and production of prostaglandins. Since oxytocin induces contractions, the inhibition of its action has been a target in the management of preterm labor. Atosiban is today the only oxytocin receptor antagonist that is available as a tocolytic. However, the quest for oxytocin receptor antagonists with a better pharmacological profile has led to the synthesis of peptide and nonpeptide molecules such as barusiban, retosiban, L-368,899, and SSR-126768A. Many of these oxytocin receptor antagonists are used only as pharmacological tools, while others have tocolytic action. In this paper, we summarize the action of oxytocin and its receptor and we present an overview of the clinical and experimental data of oxytocin antagonists and their tocolytic action.